An In Silico Cardiomyocyte Reveals the Impact of Changes in CaMKII Signalling on Cardiomyocyte Contraction Kinetics in Hypertrophic Cardiomyopathy. - Adeniran, Ismail; Wadee, Hafsa; Degens, Hans (BioMed Research International, 2024)
Hypertrophic cardiomyopathy (HCM) is characterised by asymmetric left ventricular hypertrophy, ventricular arrhythmias, and cardiomyocyte dysfunction that may cause sudden death. HCM is associated with mutations in sarcomeric proteins and is usually transmitted as an autosomal-dominant trait. The aim of this in silico study was to assess the mechanisms that underlie the altered electrophysiological activity, contractility, regulation of energy metabolism, and crossbridge cycling in HCM at the single-cell level. To investigate this, we developed a human ventricular cardiomyocyte model that incorporates electrophysiology, metabolism, and force generation. The model was validated by its ability to reproduce the experimentally observed kinetic properties of human HCM induced by (a) remodelling of several ion channels and Ca2+-handling proteins arising from altered Ca2+/calmodulin kinase II signalling pathways and (b) increased Ca2+ sensitivity of the myofilament proteins. Our simulation showed a decreased phosphocreatine-to-ATP ratio (-9%) suggesting a negative mismatch between energy expenditure and supply. Using a spatial myofilament half-sarcomere model, we also compared the fraction of detached, weakly bound, and strongly bound crossbridges in the control and HCM conditions. Our simulations showed that HCM has more crossbridges in force-producing states than in the control condition. In conclusion, our model reveals that impaired crossbridge kinetics is accompanied by a negative mismatch between the ATP supply and demand ratio. This suggests that improving this ratio may reduce the incidence of sudden death in HCM.